Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am getting stuck on this trig substitution problem.

$$\int\frac1{x^2\sqrt{x^2 - 9}}~\mathrm dx.$$

$$x = 3 \sec\theta,\qquad\theta = \sec^{-1} \sqrt{\frac{x^2}{9}},\qquad\mathrm dx = \sec\theta\ \tan\theta\ \mathrm d\theta$$

I can get to here, but I don't know how to finish it (perhaps I have made a mistake before this point?)

$$\int\frac{3\sec\theta\ \tan\theta}{9\sec^2\theta(3\sec\theta -3)}~\mathrm d\theta.$$

If anyone could help from here, I'd appreciate it.


share|improve this question
+1 For showing some work. –  JavaMan Aug 28 '11 at 18:43
If $x=3\sec\theta$, then $\theta = \sec^{-1}(x/3)$. Note that $\sqrt{x^2/9} = |x|/3$, not $x/3$. –  Arturo Magidin Aug 28 '11 at 18:46
add comment

4 Answers

up vote 3 down vote accepted

Notice first that you dropped a square root in the denominator. Also, $dx = 3 \sec \theta \tan \theta d \theta$. Otherwise, everything looked fine so far:

$$ \int \frac{1}{x^2\sqrt{x^2 - 9}}dx = \int \frac{3 \sec \theta \tan \theta}{9 \sec^2 \theta \sqrt{9 \sec^2 \theta - 9}} d \theta. $$

Now, what is a simpler way to write $\sqrt{9 \sec^2 \theta - 9}$?

share|improve this answer
Additional hint: you'll want to use $1+\tan^2\theta=\sec^2\theta$ at some point... –  J. M. Aug 28 '11 at 18:52
A simpler way would be: 3 $\sqrt{sec^2(\theta)-1}$ or 3 $\sqrt{tan^2(\theta)}$ ? –  rkMathUser Aug 28 '11 at 19:02
@rkMathUser: the second looks more helpful, then clear the square root sign (remembering tor worry about signs) –  Ross Millikan Aug 29 '11 at 12:39
add comment

I'd suggest to use the substitution $x:=3\cosh t$ instead. This leads to $$\eqalign{I&=\int{1\over 9\cosh^2 t\ 3\sinh t}\ 3\sinh t\ dt=\int{1\over 9\cosh^2 t}\ dt\cr &={1\over9}\tanh t+C={\sqrt{\cosh^2 t -1}\over9\cosh t}+C={\sqrt{x^2-9}\over 9 x}+C\ .\cr}$$

share|improve this answer
Sadly, hyperbolic functions are apparently not so familiar to the kids these days... but I upvoted anyway. –  J. M. Aug 29 '11 at 11:48
add comment

I think you made a mistake in substituting.

Added. Or rather, you made an algebra mistake. You seem to have gone from $$\sqrt{9\sec^2\theta - 9}$$ to $$3\sec\theta - 3.$$ That's incorrect. The square root does not distribute over sums and differences; that is, the square root of a difference is not the difference of the square roots (for example, $\sqrt{5} = \sqrt{9-4}$ is not equal to $\sqrt{9}-\sqrt{4} = 3-2=1$).

If $x=3\sec\theta$, then $x^2 - 9 = 9\sec^2\theta - 9 = 9(\sec^2\theta-1) = 9\tan^2\theta$, so that $\sqrt{x^2-9} = \sqrt{9\tan^2\theta} = 3|\tan\theta|$. For your substitution to work, though, you want to restrict $\theta$ to a nice interval where tangent is positive, so you can drop the absolute value bars.

share|improve this answer
add comment

Using your substitution $x=3\sec \theta $ and cancelling $\sec \theta$ in the numerator and denominator, I got

$$I=\int \frac{1}{x^{2}\sqrt{x^{2}-9}}\ \textrm{d}x=\int \frac{ \tan \theta }{3\ \sec \theta \ \sqrt{9\sec ^{2}\theta -9}}\ \textrm{d}\theta=\int \frac{\tan \theta }{9\ \sec \theta \ \sqrt{\sec ^{2}\theta -1}}\ \textrm{d}\theta.$$

It is easy to see that

$$\frac{\tan \theta }{ \sec \theta \sqrt{\sec ^{2}\theta -1}}= \cos \theta .$$


$$I=\int \frac{1}{9}\cos \theta \ \textrm{d}\theta = \dots .$$

Added. Just to confirm Christian Blatter's evaluation. $$\begin{eqnarray*} I &=&\int \frac{1}{9}\cos \theta \,d\theta =\frac{1}{9}\sin \theta +C \\ &=&\frac{1}{9}\sqrt{1-\cos ^{2}\theta }+C=\frac{1}{9}\sqrt{1-\frac{1}{\sec ^{2}\theta }} +C\\ &=&\frac{1}{9}\sqrt{1-\frac{9}{x^{2}}}+C=\frac{\sqrt{x^{2}-9}}{9x}+C. \end{eqnarray*}$$

share|improve this answer
add comment

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.